2021
DOI: 10.1155/2021/6680204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Shear Resistance of Carex‐Root‐Fibered Soil

Abstract: Carex shows strong vitality, adaptability, and performance with regard to soil consolidation and slope protection but is often disregarded as a weed. This study proposes to turn this so-called weed into treasure, using its characteristics to protect the slope. We studied the interaction between the carex roots and soil and compared it to other types of grass. To understand the interaction between the carex roots and soil, this study investigated the tensile properties of the carex root fibers. The effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Lian, B's study shows that the individual horizontal and vertical arrangement is not as effective as the crossed arrangement because it is reinforced in only one direction compared to the crossed arrangement. Moreover, the reinforcement effect of vertical roots is better than that of horizontal arrangement 24 . In this paper, the diameters and lengths of the root systems added in the experiments were selected according to uniform criteria, and the basic difference between the two root distribution patterns was the proportion of roots in different directions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lian, B's study shows that the individual horizontal and vertical arrangement is not as effective as the crossed arrangement because it is reinforced in only one direction compared to the crossed arrangement. Moreover, the reinforcement effect of vertical roots is better than that of horizontal arrangement 24 . In this paper, the diameters and lengths of the root systems added in the experiments were selected according to uniform criteria, and the basic difference between the two root distribution patterns was the proportion of roots in different directions.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the study of root distribution properties, Zhang et al 22 and Lian et al 23 investigated the effects of three analytical distributions, vertical, horizontal, and cross, on the shear strength of root-soil complexes by triaxial compression tests and suggested that the enhancement effect of cross root distribution was optimal. Wang et al 24 tested four types of herbaceous…”
mentioning
confidence: 99%
“…When the slope loses water the soil shrinks and consequently fissures are created. Repeated expansion and contraction lead to the loosening of the swelling soil and t form many irregular fissures in it, thus creating conditions for further erosion of the soil surface [12][13][14][15]. In the event of rainfall infiltration, it is very likely to lead to geological disasters such as landslides [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%